Effects of the neuromuscular training in the cardiorespiratory fitness and body composition of female volleyball athletes - Simoes, R. A.; Salles, G. S. L. M.; Gonelli, P. R. G.; Leite, G. dos Santos; Dias, R.; Cavaglieri, C. R.; Pellegrinotti, I. L.; Borin, J. P.; Verlengia, R.; Alves, S. C. C.; de Castro, C. M. (Revista Brasileira de Medicina do Esporte, 2009)
The responses of the human body submitted to several stimuli measured by performance parameters have been object of studies in order to improve training methods. The aim of this study was to investigate the effects of the neuromuscular training in the cardiorespiratory fitness and body composition of volleyball athletes. Eleven women were assessed before and after 12 weeks of training, concerning the preparatory phase of the annual training cycle. The experimental protocol consisted of assessment of the body composition (fat percentage, lean mass and body fat) and of the cardiorespiratory fitness through ergospirometry on treadmill with continuous protocol and increasing load, in which the oxygen maximal uptake, maximum heart rate, anaerobic threshold, heart rate threshold and anaerobic threshold velocity were determined. The training was carried out five times per week and was divided in two sessions: one strength training and the another technical and tactical training. After the studied period, increase (p < 0.05) in oxygen maximal uptake (6.5%), anaerobic threshold (17.5%), threshold velocity (15.3%) and lean mass (3.2%) was observed. Reduction (p< 0.05) in maximum heart rate (- 3.1%), fat percentage (-8.2%) and body fat (-7.4%) was observed. It is concluded that neuromuscular training performed in the preparatory phase contributed to increase in the cardiorespiratory fitness and lean mass as well as decrease in fat percentage and body fat of volleyball athletes.